Monolithic copper-based catalyst for hydrogen production from methanol steam reforming and preparation method thereof
By using integral copper-based catalysts prepared with raw materials such as copper spinel, the problems of mass transfer and heat transfer in small distributed scenarios in the prior art are solved, and the mechanical strength and active component loading of the catalyst are improved. , achieving more efficient methanol conversion rate and longer service life.
Patent Information
- Application Number
- CN202311222008.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-21
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2043-09-21
AI Technical Summary
In the prior art, copper-based catalysts used for hydrogen reforming methanol steam reforming have mass transfer and heat transfer problems in small distributed scenarios, and the active components of the integrated catalyst are low, the process is complex, and the coating firmness is strong. and insufficient uniformity and limited service life.
The copper spinel, binder, pore-forming agent and silicon carbide are used as raw materials to prepare the integrated copper-based catalyst by ball mill mixing, dry press forming and high-temperature sintering, and use the high-temperature resistance of copper spinel to protect the active group. to increase the mechanical strength of the catalyst and the loading of active components.
The catalyst has high mechanical strength, high loading of active components and low component loss rate, which simplifies the preparation process and improves the catalytic performance and service life of the catalyst.
Smart Images

Figure CN117123248B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of catalyst preparation, and in particular to an integral copper-based catalyst for hydrogen production by methanol steam reforming and a preparation method thereof. Background Art
[0002] Methanol, as a widely available hydrogen energy carrier, can produce hydrogen through methanol steam reforming reaction. It has the advantages of economy and convenience in distributed scenarios. This technology has been widely studied in recent years.
[0003] The catalysts used for methanol steam reforming to produce hydrogen are mainly divided into two categories: precious metals and non-precious metals. Non-precious metals are mainly copper-based catalysts, which have become the first choice for methanol steam reforming hydrogen production catalysts in commercial distributed hydrogen production devices due to their advantages such as good low-temperature activity, high hydrogen selectivity and low price.
[0004] Industrial methanol steam reforming hydrogen production equipment often uses copper-based catalysts of original particle size. When applied to small distributed scenarios, the catalytic reaction will face greater mass transfer and heat transfer problems. At this time, using a strong thermal conductive substrate to load copper active components to form an integral catalyst is conducive to the process intensification of the catalytic reaction and improve the activity of the catalyst. The silicon carbide ceramic substrate has a high thermal conductivity coefficient. When used in methanol steam reforming reactions, it can couple the endothermic characteristics of the reaction, eliminate the cold spots of the catalyst bed, and improve the overall catalytic efficiency of the catalyst.
[0005] Currently, there are two main methods for preparing monolithic catalysts on a silicon carbide substrate. One is to impregnate the precursor material into the silicon carbide substrate and then calcine it to generate the required active components in situ (CN110639570A, CN113000057A). The other is to load a prefabricated powder catalyst on the silicon carbide substrate by slurry coating (Wang, Y. International Journal of Hydrogen Energy 2021, 46(51), 25878-25892).
[0006] These loading methods all have the problem of low single loading amount of catalyst active components, so they need to be repeatedly impregnated, dried, and calcined. The process is complicated and cumbersome, and there are problems with poor coating firmness and uniformity, which limits the service life in the process of on-board methanol reforming to produce hydrogen. Summary of the invention
[0007] The present invention provides an integral copper-based catalyst for hydrogen production by methanol steam reforming and a preparation method thereof. The integral catalyst has the advantages of high mechanical strength, high active component loading, low component loss rate, etc., and the preparation process is simple and easy to operate, and is green, environmentally friendly and pollution-free.
[0008] The technical solution of the present invention is as follows:
[0009] A method for preparing a monolithic copper-based catalyst for hydrogen production by methanol steam reforming, comprising: using copper spinel, a binder, a pore former and silicon carbide as raw materials, ball-milling and mixing the raw materials uniformly, and then dry-pressing and high-temperature sintering to obtain a monolithic catalyst;
[0010] The mass ratio of copper spinel, binder, pore former and silicon carbide is (1-2):(0.5-1):(1-6):(3-7.5).
[0011] The present invention uses copper spinel, a binder, a pore-forming agent and silicon carbide as raw materials to form a monolithic copper-based catalyst in one pot. At the same time, since the copper spinel powder is sintering-resistant, it can effectively protect active species during the high-temperature sintering process of the structural substrate, so that the prepared monolithic catalyst has the advantages of high mechanical strength, high active component loading, low component loss rate, etc.
[0012] Preferably, the copper spinel is at least one of copper aluminum spinel, copper gallium spinel, copper manganese spinel and copper iron spinel.
[0013] Copper spinel can be obtained by precipitation method.
[0014] Most preferably, the copper spinel is copper aluminum spinel. When copper aluminum spinel is used as the raw material, the obtained monolithic copper-based catalyst has a more excellent catalytic activity.
[0015] Preferably, the adhesive is glass frit and / or aluminum dihydrogen phosphate.
[0016] Preferably, the pore-forming agent is at least one of polymethyl methacrylate (PMMA), graphite, and carbon nanotubes.
[0017] Further preferably, the pore former is polymethyl methacrylate. The type of pore former affects the activity of the catalyst. PMMA, which is easy to decompose, is the first choice for in-situ pore formers, while graphite or carbon nanotubes, which are not easy to decompose, still have a large amount of residues after sintering. The residual carbon reduces mass transfer and reduces the catalytic activity.
[0018] Preferably, the particle size of the pore-forming agent is 200-2000 mesh.
[0019] The raw material ratio directly affects the catalyst's compressive strength, methanol conversion rate, porosity and other parameters. A higher content of silicon carbide and a lower content of pore-forming agent are beneficial to improving the compressive strength, but reducing the porosity, indicating that the catalyst activity is limited by the diffusion of reactants. At the same time, this process can easily achieve a high loading of active components in the monolithic catalyst, and the catalytic activity can be significantly improved.
[0020] Preferably, the mass ratio of copper spinel, binder, pore former and silicon carbide is (1-2):0.5:(4-5):(3-6).
[0021] Preferably, the ball milling speed is 350-550 rpm, and the ball milling time is 0.5-8 hours. Ball milling allows the raw materials to be fully mixed and evenly mixed, and ultimately the active components in the prepared monolithic copper-based catalyst are evenly distributed, thereby improving the catalytic activity of the catalyst.
[0022] Preferably, the dry pressing pressure is 5 to 30 MPa.
[0023] The sintering temperature affects the mechanical properties and catalytic activity of the monolithic copper-based catalyst. When the sintering temperature is too low, the active component silicon carbide powder cannot be effectively bonded together, resulting in poor mechanical strength of the catalyst and easy collapse of the skeleton; when the sintering temperature is too high, the mechanical strength is enhanced, but the catalytic activity decreases. It is necessary to balance the relationship between catalyst performance and mechanical strength.
[0024] Preferably, the high temperature sintering temperature is 450-1000°C; more preferably 450-800°C; more preferably 500-600°C.
[0025] The sintering time also affects the mechanical properties and catalytic activity of the catalyst. When the sintering time is too short, the pore-forming agent cannot be effectively removed, and the carbon layer will cover the active components, causing the catalytic activity to decrease. As the sintering time increases, the mechanical strength of the catalyst is further improved, but the catalytic activity decreases.
[0026] Preferably, the high temperature sintering time is 1-5 h; more preferably, it is 2-5 h.
[0027] The high temperature sintering atmosphere is air atmosphere.
[0028] The present invention also provides an integral copper-based catalyst prepared by the above preparation method.
[0029] Compared with the prior art, the present invention has the following beneficial effects:
[0030] (1) The preparation method of the present invention utilizes the high temperature sintering property of copper spinel to in-situ add the catalyst active components during the silicon carbide powder molding process, thereby avoiding the shortcomings of the previous coating method such as cumbersome steps, low active component loading and uneven distribution, and conveniently realizing the industrial production of methanol hydrogen production monolithic copper-based catalyst, and has the advantages of easily achieving high active component loading, simple operation, and components not easy to fall off;
[0031] (2) The preparation method of the present invention uses an integrated molding technology, which is beneficial to the fixation and dispersion of the active components, avoiding sintering, migration and loss during the roasting process, and the prepared catalyst has stronger catalytic performance; at the same time, the catalyst is more stable, the catalyst components are not easily lost during use, and the service life is longer;
[0032] (3) The integral copper-based catalyst prepared by the present invention is used in the methanol steam reforming hydrogen production reaction and has a high methanol conversion rate and a long service life. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 This is a stability comparison chart of the monolithic copper-based catalysts prepared in Example 2 and Comparative Example 9. DETAILED DESCRIPTION
[0034] Comparative Example 1
[0035] Copper aluminum spinel, glass material, PMMA and silicon carbide powder were accurately weighed in a mass ratio of 1:0.5:5:4, mixed evenly by mechanical ball milling to obtain catalyst precursor powder, which was put into a mold for dry pressing. After high-temperature sintering at 400°C for 3 hours, it was found that the integral catalyst was very brittle and had not been formed.
[0036] Example 1
[0037] Copper aluminum spinel, glass frit, PMMA and silicon carbide powder were accurately weighed in a mass ratio of 1:0.5:5:4, and after mechanical ball milling and mixing, a catalyst precursor powder was obtained, which was placed in a mold for dry pressing. After sintering at 500°C for 3 hours, a monolithic copper-based catalyst for hydrogen production by methanol steam reforming was obtained. Its compressive strength is 7.5Mpa and its porosity is 65%. The monolithic catalyst was loaded into a reactor, hydrogen reduction gas was introduced, and the catalyst was reduced at 250°C for 3 hours, and then methanol reforming hydrogen production reaction was carried out. The reaction product was analyzed by gas chromatography, and the methanol conversion rate was 90% and the hydrogen selectivity was 74.9%.
[0038] Example 2
[0039] Copper aluminum spinel, glass frit, PMMA and silicon carbide powder were accurately weighed in a mass ratio of 1:0.5:5:4, and after mechanical ball milling and mixing, a catalyst precursor powder was obtained, which was placed in a mold for dry pressing. After sintering at 600°C for 3 hours, a monolithic copper-based catalyst for methanol steam reforming hydrogen production was obtained. Its compressive strength is 10.3Mpa and its porosity is 61%. The monolithic catalyst was loaded into a reactor, hydrogen reduction gas was introduced, and the catalyst was reduced at 250°C for 3 hours, and then methanol reforming hydrogen production reaction was carried out. The reaction product was analyzed by gas chromatography, and the methanol conversion rate was 81% and the hydrogen selectivity was 74.5%.
[0040] Example 3
[0041] Copper aluminum spinel, glass material, PMMA and silicon carbide powder were accurately weighed in a mass ratio of 1:0.5:5:4, and after mechanical ball milling and mixing, a catalyst precursor powder was obtained, which was placed in a mold for dry pressing. After sintering at 1000°C for 3 hours, a monolithic copper-based catalyst for hydrogen production by methanol steam reforming was obtained. Its compressive strength is 12.3Mpa and its porosity is 58%. The monolithic catalyst was loaded into a reactor, hydrogen reduction gas was introduced, and the catalyst was reduced at 250°C for 3 hours, and then methanol reforming hydrogen production reaction was carried out. The reaction product was analyzed by gas chromatography, and the methanol conversion rate was 64% and the hydrogen selectivity was 74.3%.
[0042] Example 4
[0043] Copper aluminum spinel, glass frit, PMMA and silicon carbide powder were accurately weighed in a mass ratio of 1:0.5:5:4, and after mechanical ball milling and mixing, a catalyst precursor powder was obtained, which was placed in a mold for dry pressing. After sintering at 600°C for 1h, a monolithic copper-based catalyst for methanol steam reforming hydrogen production was obtained. Its compressive strength is 5.6Mpa and its porosity is 51%. The monolithic catalyst was loaded into a reactor, hydrogen reduction gas was introduced, and the catalyst was reduced at 250°C for 3h, and then methanol reforming hydrogen production reaction was carried out. The reaction product was analyzed by gas chromatography, and the methanol conversion rate was 34% and the hydrogen selectivity was 73.6%.
[0044] Example 5
[0045] Copper aluminum spinel, glass frit, PMMA and silicon carbide powder were accurately weighed in a mass ratio of 1:0.5:5:4, and the catalyst precursor powder was obtained after being evenly mixed by mechanical ball milling. The catalyst precursor powder was placed in a mold for dry pressing and sintered at 600°C for 2 hours to obtain a monolithic copper-based catalyst for methanol steam reforming hydrogen production. Its compressive strength is 8.9Mpa and its porosity is 59%. The monolithic catalyst was loaded into a reactor, hydrogen reduction gas was introduced, and the catalyst was reduced at 250°C for 3 hours, and then methanol reforming hydrogen production reaction was carried out. The reaction product was analyzed by gas chromatography, and the methanol conversion rate was 72% and the hydrogen selectivity was 74.3%.
[0046] Example 6
[0047] Copper aluminum spinel, glass frit, PMMA and silicon carbide powder were accurately weighed in a mass ratio of 1:0.5:5:4, and after mechanical ball milling and mixing, a catalyst precursor powder was obtained, which was placed in a mold for dry pressing. After sintering at 600°C for 5 hours, a monolithic copper-based catalyst for methanol steam reforming hydrogen production was obtained. Its compressive strength is 10.9Mpa and its porosity is 61%. The monolithic catalyst was loaded into a reactor, hydrogen reduction gas was introduced, and the catalyst was reduced at 250°C for 3 hours, and then methanol reforming hydrogen production reaction was carried out. The reaction product was analyzed by gas chromatography, and the methanol conversion rate was 78% and the hydrogen selectivity was 74.5%.
[0048] Example 7
[0049] Copper aluminum spinel, aluminum dihydrogen phosphate, PMMA and silicon carbide powder were accurately weighed in a mass ratio of 1:0.5:5:4, and after mechanical ball milling and mixing, a catalyst precursor powder was obtained, which was placed in a mold for dry pressing. After sintering at 1000°C for 3 hours, a monolithic copper-based catalyst for methanol steam reforming hydrogen production was obtained. Its compressive strength is 14.6Mpa and its porosity is 52%. The monolithic catalyst was loaded into a reactor, hydrogen reduction gas was introduced, and the catalyst was reduced at 250°C for 3 hours, and then methanol reforming hydrogen production reaction was carried out. The reaction product was analyzed by gas chromatography, and the methanol conversion rate was 61% and the hydrogen selectivity was 74.2%.
[0050] Example 8
[0051] Copper iron spinel, glass material, PMMA and silicon carbide powder were accurately weighed in a mass ratio of 1:0.5:5:4, and the catalyst precursor powder was obtained after being evenly mixed by mechanical ball milling. The catalyst precursor powder was placed in a mold for dry pressing and sintered at 600°C for 3 hours to obtain a monolithic copper-based catalyst for methanol steam reforming hydrogen production. The compressive strength is 10.8Mpa and the porosity is 60%. The monolithic catalyst was loaded into a reactor, hydrogen reduction gas was introduced, and the catalyst was reduced at 250°C for 3 hours, and then the methanol reforming hydrogen production reaction was carried out. The reaction product was analyzed by gas chromatography, and the methanol conversion rate was 44% and the hydrogen selectivity was 74.2%.
[0052] Example 9
[0053] Copper gallium spinel, glass material, PMMA and silicon carbide powder were accurately weighed in a mass ratio of 1:0.5:5:4, and after mechanical ball milling and mixing, a catalyst precursor powder was obtained, which was placed in a mold for dry pressing. After sintering at 600°C for 3 hours, a monolithic copper-based catalyst for methanol steam reforming hydrogen production was obtained. Its compressive strength is 10.7Mpa and its porosity is 61%. The monolithic catalyst was loaded into a reactor, hydrogen reduction gas was introduced, and the catalyst was reduced at 250°C for 3 hours, and then methanol reforming hydrogen production reaction was carried out. The reaction product was analyzed by gas chromatography, and the methanol conversion rate was 36% and the hydrogen selectivity was 73.6%.
[0054] Example 10
[0055] Copper manganese spinel, glass frit, PMMA and silicon carbide powder were accurately weighed in a mass ratio of 1:0.5:5:4, and after mechanical ball milling and mixing, a catalyst precursor powder was obtained, which was placed in a mold for dry pressing. After sintering at 600°C for 3 hours, a monolithic copper-based catalyst for methanol steam reforming hydrogen production was obtained. Its compressive strength is 10.8Mpa and its porosity is 61%. The monolithic catalyst was loaded into a reactor, hydrogen reduction gas was introduced, and the catalyst was reduced at 250°C for 3 hours, and then methanol reforming hydrogen production reaction was carried out. The reaction product was analyzed by gas chromatography, and the methanol conversion rate was 58% and the hydrogen selectivity was 74.3%.
[0056] Embodiment 11
[0057] Copper aluminum spinel, glass frit, graphite powder and silicon carbide powder were accurately weighed in a mass ratio of 1:0.5:5:4, and after mechanical ball milling and mixing, a catalyst precursor powder was obtained, which was placed in a mold for dry pressing. After sintering at 600°C for 3 hours, a monolithic copper-based catalyst for methanol steam reforming hydrogen production was obtained. Its compressive strength is 8.3Mpa and its porosity is 58%. The monolithic catalyst was loaded into a reactor, hydrogen reduction gas was introduced, and the catalyst was reduced at 250°C for 3 hours, and then methanol reforming hydrogen production reaction was carried out. The reaction product was analyzed by gas chromatography, and the methanol conversion rate was 68% and the hydrogen selectivity was 74.6%.
[0058] Example 12
[0059] Copper aluminum spinel, glass frit, PMMA and silicon carbide powder were accurately weighed in a mass ratio of 1:0.5:4:6, and after mechanical ball milling and mixing, a catalyst precursor powder was obtained, which was placed in a mold for dry pressing. After sintering at 600°C for 3 hours, a monolithic copper-based catalyst for methanol steam reforming hydrogen production was obtained. Its compressive strength is 12.8Mpa and its porosity is 48%. The monolithic catalyst was loaded into a reactor, hydrogen reduction gas was introduced, and the catalyst was reduced at 250°C for 3 hours, and then methanol reforming hydrogen production reaction was carried out. The reaction product was analyzed by gas chromatography, and the methanol conversion rate was 69% and the hydrogen selectivity was 74.5%.
[0060] Example 13
[0061] Copper aluminum spinel, glass frit, PMMA and silicon carbide powder were accurately weighed in a mass ratio of 2:0.5:5:3, and after mechanical ball milling and mixing, a catalyst precursor powder was obtained, which was placed in a mold for dry pressing. After sintering at 600°C for 3 hours, a monolithic copper-based catalyst for methanol steam reforming hydrogen production was obtained. Its compressive strength is 10.4Mpa and its porosity is 62%. The monolithic catalyst was loaded into a reactor, hydrogen reduction gas was introduced, and the catalyst was reduced at 250°C for 3 hours, and then methanol reforming hydrogen production reaction was carried out. The reaction product was analyzed by gas chromatography, and the methanol conversion rate was 100% and the hydrogen selectivity was 74.6%.
[0062] Comparative Example 2
[0063] The copper-zinc-aluminum powder catalyst, glass material, PMMA and silicon carbide powder were accurately weighed in a mass ratio of 1:0.5:5:4, and the catalyst precursor powder was obtained after being evenly mixed by mechanical ball milling. The catalyst precursor powder was placed in a mold for dry pressing and sintered at 600°C to obtain a monolithic copper-based catalyst for hydrogen production by methanol steam reforming. The compressive strength is 9.9Mpa and the porosity is 63%. The monolithic catalyst was loaded into a reactor, hydrogen reduction gas was introduced, and the catalyst was reduced at 250°C for 3h, and then the methanol reforming hydrogen production reaction was carried out. The reaction product was analyzed by gas chromatography, and the methanol conversion rate was 18% and the hydrogen selectivity was 74.4%.
[0064] Comparative Example 3
[0065] The CuO / ZnO powder catalyst, glass material, PMMA and silicon carbide powder were accurately weighed in a mass ratio of 1:0.5:5:4, and the catalyst precursor powder was obtained after being evenly mixed by mechanical ball milling. The catalyst precursor powder was placed in a mold for dry pressing and sintered at 600°C to obtain a monolithic copper-based catalyst for hydrogen production by methanol steam reforming. The compressive strength was 10.4Mpa and the porosity was 62%. The monolithic catalyst was loaded into a reactor, hydrogen reduction gas was introduced, and the catalyst was reduced at 250°C for 3h, and then the methanol reforming hydrogen production reaction was carried out. The reaction product was analyzed by gas chromatography, and the methanol conversion rate was 14% and the hydrogen selectivity was 72.5%.
[0066] Comparative Example 4
[0067] The CuO / ZnO / CeO2 powder catalyst, glass material, PMMA and silicon carbide powder were accurately weighed in a mass ratio of 1:0.5:5:4, and the catalyst precursor powder was obtained after being evenly mixed by mechanical ball milling. The catalyst precursor powder was placed in a mold for dry pressing and sintered at 600°C to obtain a monolithic copper-based catalyst for hydrogen production by methanol steam reforming. The compressive strength is 10.2Mpa and the porosity is 62%. The monolithic catalyst was loaded into a reactor, hydrogen reduction gas was introduced, and the catalyst was reduced at 250°C for 3h, and then the methanol reforming hydrogen production reaction was carried out. The reaction product was analyzed by gas chromatography, and the methanol conversion rate was 47% and the hydrogen selectivity was 73.9%.
[0068] Comparative Example 5
[0069] The CuO / SiO2 powder catalyst, glass material, PMMA and silicon carbide powder were accurately weighed in a mass ratio of 1:0.5:5:4, and the catalyst precursor powder was obtained after being evenly mixed by mechanical ball milling. The catalyst precursor powder was placed in a mold for dry pressing and sintered at 600°C to obtain a monolithic copper-based catalyst for hydrogen production by methanol steam reforming. The compressive strength is 10.2Mpa and the porosity is 61%. The monolithic catalyst was loaded into a reactor, hydrogen reduction gas was introduced, and the catalyst was reduced at 250°C for 3h, and then the methanol reforming hydrogen production reaction was carried out. The reaction product was analyzed by gas chromatography, and the methanol conversion rate was 50% and the hydrogen selectivity was 73.5%.
[0070] Comparative Examples 6 to 9
[0071] Disperse 14g of pseudo-boehmite powder in 140mL of deionized water and stir to fully disperse it. Then add an appropriate amount of concentrated nitric acid to a pH of about 3, and continue stirring until it becomes a white translucent sol-like liquid. Place silicon carbide ceramics without active components in the pseudo-boehmite sol to coat the alumina coating, immerse for 60 minutes, then blow off the excess liquid with a wind gun, dry at 80℃ for h, heat from room temperature to 550℃ at a rate of 3℃ / min, keep constant temperature for 4h, and take out after naturally cooling to room temperature. According to the number of times of coating alumina 1 to 4 times, the corresponding proportions are 6 to 9. After the alumina coating is completed, the obtained Al2O3 / SiC is placed in the above-mentioned 1M copper nitrate aqueous solution, immersed for 60 minutes, then blow off the excess liquid with a wind gun, dry at room temperature for 24h, and then dry at 110℃ for 6h, heat from room temperature to 750℃ at a rate of 3℃ / min and keep constant temperature for 3h to form copper-aluminum spinel on the alumina surface, and take out after naturally cooling to room temperature.
[0072] The comparison of the integrated preparation conditions and performance parameters of the copper-based silicon carbide ceramic monolithic catalysts in Comparative Examples 1-5 and Examples 1-13 is shown in Table 1.
[0073] The comparison of preparation conditions and performance parameters of copper-based supported silicon carbide ceramic monolithic catalysts in Comparative Examples 6-9 is shown in Table 2.
[0074] Table 1
[0075]
[0076]
[0077] Table 2
[0078]
[0079] By comparing Comparative Example 1 and Examples 1-3, it is found that the sintering temperature affects the mechanical properties and catalytic activity of the integral catalyst. At too low a sintering temperature, the active component silicon carbide powder cannot be effectively bonded together, causing the skeleton to collapse. When the sintering temperature is 500°C, the compressive strength of the catalyst is 7.5MPa, and the methanol conversion rate is 90%; when the sintering temperature is 600°C, the compressive strength of the catalyst is 10.3MPa, and the methanol conversion rate is 81%; when the sintering temperature is 1000°C, the compressive strength of the catalyst is 12.3MPa, but the methanol conversion rate drops to 57%, indicating that the catalyst activity is affected by high temperature, so it is necessary to balance the relationship between catalyst performance and mechanical strength.
[0080] By comparing Examples 2, 4-6, it was found that the sintering time also affects the compressive strength and catalytic activity of the catalyst. When the sintering time is 1 hour, the pore-forming agent cannot be effectively removed. At this time, the carbon layer will cover the active components, causing the catalytic activity to decrease. With the increase of the sintering time, after sintering for 3 hours, the compressive strength of the catalyst is 10.3MPa, and the methanol conversion rate is 81%. When the sintering time is further increased to 5 hours, the mechanical strength further increases to 10.9Mpa, but the methanol conversion rate decreases to 78%.
[0081] By comparing Examples 3 and 7, it can be found that different binders affect the compressive strength, methanol conversion rate, and porosity of the integral catalyst. Aluminum dihydrogen phosphate has stronger bonding properties at high temperatures, which makes the integral catalyst have higher mechanical strength, but at the same time causes the active components to be partially embedded in the base skeleton, resulting in a decrease in catalytic activity.
[0082] By comparing Examples 2, 8-10, it can be found that among many copper spinels (copper aluminum spinel, copper iron spinel, copper manganese spinel, copper gallium spinel), copper aluminum spinel as a formed active component has better activity than copper iron spinel.
[0083] By comparing Examples 2 and 11, it can be found that the type of pore former affects the activity of the catalyst. PMMA, which is easily decomposed, is the first choice for the in-situ pore former, while graphite, which is not easy to decompose, still has a large amount of residue after sintering. The residual carbon reduces mass transfer and reduces the catalytic activity.
[0084] By comparing Examples 2, 12, and 13, it can be found that the raw material ratio directly affects the compressive strength, methanol conversion rate, porosity, and other parameters. A higher content of silicon carbide and a lower content of pore-forming agent are beneficial to improving the compressive strength, but reducing the porosity, indicating that the catalyst activity is limited by the diffusion of reactants. At the same time, the process can easily achieve a high loading of active components in the monolithic catalyst, and the catalytic activity can be significantly improved.
[0085] By comparing Example 2 with Comparative Examples 2 to 5, it is found that when CuO / ZnO, CuO / ZnO / CeO2, CuO / SiO2, and commercial copper-zinc-aluminum catalysts are used as active components, the methanol conversion rate of the monolithic catalyst is not as good as that of copper-aluminum spinel. This is because the active components in CuO / ZnO, CuO / ZnO / CeO2, CuO / SiO2, and commercial copper-zinc-aluminum catalysts have poor sintering resistance and are difficult to withstand the high-temperature sintering process after dry pressing. The copper spinel catalyst itself has strong sintering resistance and has unique advantages in the one-pot preparation of monolithic copper-based catalysts.
[0086] By comparing Example 2 with Comparative Examples 6 to 9, it is found that when the coating method is used to load the aluminum oxide coating and copper active species, the number of coatings must be guaranteed to be more than 3 times to achieve a methanol conversion rate equivalent to that of Example 2. This is because the aluminum oxide coating applied in a single time is small, and the loading amount of the copper active component in the subsequent step cannot be guaranteed. The use of an integrated molding method facilitates the loading amount of the active component, which has its unique advantages over the traditional coating method.
[0087] Catalyst stability test
[0088] The monolithic copper-based catalyst prepared in Example 2 was treated with ultrasound for 30 minutes, and the mass loss was only 0.52%, which is far better than that reported in the literature (Liao M. International Journal of Hydrogen Energy, 2020, 45(41): 20922-20932), (Sanz O. International Journal of Hydrogen Energy, 2016, 41(10): 5250-5259), and (Zhou W. Fuel, 2017, 191: 46-53).
[0089] The monolithic copper-based catalyst prepared in Example 2 and Comparative Example 9 was loaded into a reactor, hydrogen reducing gas was introduced, and the catalyst was reduced at 250° C. for 3 h, and then methanol reforming hydrogen production reaction was carried out. The reaction products were analyzed by gas chromatography. The results are as follows: Figure 1 As shown, it can be seen that compared with conventional catalysts, the integral copper-based catalyst prepared by the present invention has more stable catalytic activity and longer service life.
[0090] The embodiments described above provide a detailed description of the technical solutions and beneficial effects of the present invention. It should be understood that the above are only specific embodiments of the present invention and are not intended to limit the present invention. Any modifications, supplements and equivalent substitutions made within the scope of the principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a monolithic copper-based catalyst for hydrogen production by methanol steam reforming, characterized in that: include: Copper spinel, binder, pore former and silicon carbide are used as raw materials, the raw materials are ball-milled and mixed evenly, and then dry-pressed and sintered at a high temperature of 450-1000°C to obtain a monolithic catalyst; the mass ratio of copper spinel, binder, pore former and silicon carbide is (1-2): (0.5-1): (1-6): (3-7.5); The copper spinel is at least one of copper aluminum spinel, copper gallium spinel, copper manganese spinel and copper iron spinel.
2. The method for preparing a monolithic copper-based catalyst for hydrogen production by methanol steam reforming according to claim 1, characterized in that: The mass ratio of copper spinel, binder, pore former and silicon carbide is (1-2):0.5:(4-5):(3-6).
3. The method for preparing a monolithic copper-based catalyst for hydrogen production by methanol steam reforming according to claim 1, characterized in that: The binder is glass frit and / or aluminum dihydrogen phosphate.
4. The method for preparing a monolithic copper-based catalyst for hydrogen production by methanol steam reforming according to claim 1, characterized in that: The pore-forming agent is at least one of polymethyl methacrylate, graphite and carbon nanotubes.
5. The method for preparing a monolithic copper-based catalyst for hydrogen production by methanol steam reforming according to claim 1, characterized in that: The ball milling speed was 350~550 rpm, and the ball milling time was 0.5~8 h.
6. The method for preparing a monolithic copper-based catalyst for hydrogen production by methanol steam reforming according to claim 1, characterized in that: The dry pressing pressure is 5~30 MPa.
7. The method for preparing a monolithic copper-based catalyst for hydrogen production by methanol steam reforming according to claim 1, characterized in that: The high temperature sintering time is 1-5h.
8. An integral copper-based catalyst for hydrogen production by methanol steam reforming, characterized in that: The preparation is obtained by the preparation method according to any one of claims 1 to 7.
Citation Information
Patent Citations
Monolithic catalyst and preparation method and application thereof, and method for producing hydrogen by methanol steam reforming by using monolithic catalyst
CN110639570A
Preparation method and application of porous material loaded with Cu / ZnO / CeO2 catalyst
CN113000057A
Improved method for producing hydrogen cyanide through catalytic dehydration of gaseous formamide-direct heating
CN102015532A
Copper-aluminum spinel catalyst for hydrogen production through methanol reforming, and preparation method and application thereof
CN113198471A